PHYTOCHEMICAL ANALYSES AND ANTI- MICROBIAL ACTIVITIES OF THE LEAF AND STEM BARK EXTRACTS OF GARCINIA KOLA - HERKEL (FAMILY GULTIFERAE) (Biological Sciences - PJSIR, 2004)
Preliminary phytochemical analyses carried out on the leaves and stem bark extracts of Garcinia kola revealed the presence of glycosides, saponins, tannins and flavonoids. Alkaloids were present only in the leaf extract. Thin layer chromatogra- phy (TLC) on silica gel using different solvent systems showed the alkaloids to be both of salt and basic forms. Different con- centrations of methanolic extracts (50mg/ml, 100mg/ml, 150mg/ml and 200mg/ml) were tested on cultures of bacteria and fungi to determine their sensitivity and minimum inhibi- tory concentrations (MIC). Antibiotic gentamycin (1mg/ml) was used as the standard drug. The stem bark and leaf extracts of Garcinia kola had very high inhibitory activities, only on Staphylococcus aureus with MIC of 100mg / ml and 150mg/ml, respectively. The stem bark and leaves of this plant can be used for the treatment of diseases caused by Staphylococcus aureus.